Sports participation and cultural identity in the experience of young people - Maniam, Vegneskumar 1979- (Bern Peter Lang, 2014)
This book focuses on inclusion and exclusion in sporting activities among young people in a multicultural society. Do young people who identify with cultural groups other than the majority experience exclusion from sporting teams, or do they find themselves readily included? Does this vary across identities, and sports? In the context of Australia, where sport is an integral part of national life and one in four of the population were born overseas, and over 270 different ancestries are acknowledged, young people were asked to write about their cultural identity and their experiences playing sport. Using a humanistic sociological approach, the inductive analysis justaposed their sense of cultural identity with their participation or non-participation in sport, and with the particular sports played. This book is important for all those in culturally diverse society especially academics, teachers and sports administrators, who are interested in the issue of exclusion and inclusion of cultural minorities in sport. -- Back cover
Introduction : Sport and Multiculturalism in the Global Context -- Theorizing Cultural Identity and Sports Participation -- Personal Documents as Research Data -- Respondents' Sense of Cultural Identity -- Reasons for Playing or Not Playing Sport -- Participation of the Culturally Diverse in Particular Sports -- Cultural Identity in Inclusive and Exclusive Experiences of Sport -- Conclusion : Implication for Inclusive Experience of Sport in Multicultural Context.
Includes bibliographical references and index.
Keywords: Sports -- Social aspects -- Australia; Marginality, Social -- Australia; Group identity -- Australia